Nuclear contours in Fala in conversational and read speech: Similarities and differences with Spanish, Galician and Portuguese - Elordieta, Gorka; Masa, Lucía (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
In this work we describe the most frequent nuclear configurations in declarative utterances and absolute and partial interrogative utterances of Fala, a language of the Galician-Portuguese family spoken in Sierra de Gata (in Extremadura, Spain). Fala is composed of three varieties: Valverdeiru, Lagarteiru and Mañegu. 12 speakers have been recorded in conversational and read speech. We compare the main nuclear contours of Fala with the languages of its family (Galician and Portuguese), and with the contact language (Spanish). Valverdeiru shows more influence from Castilian Spanish, and Lagarteiru and the Mañegu share some features with Galician and European Portuguese.